2013
DOI: 10.4103/1319-2442.111031
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and sleep in hemodialysis patients

Abstract: The purpose of this study was to determine the quality of life and sleep of chronic hemodialysis (HD) patients. Quality of sleep was measured using the Pittsburgh Sleep Quality Index (PSQI) and quality of life (QoL) was measured using the Medical Outcomes Study 36-item Short Form (SF-36) in 115 HD patients. One hundred (87%) patients were "poor sleepers" (global PSQI ≥5). The SF-36 mental component summary and physical component summary (PCS) scores were higher than 50 only in 43% and 32% of the subjects, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
42
4
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 0 publications
7
42
4
4
Order By: Relevance
“…Most of the studies found no correlation between having diabetes mellitus and quality of sleep in patients under chronic hemodialysis (2,10,11,13,24). On the other hand, we and Einollahi et al (23) observed a lower quality of sleep in patients with diabetes mellitus.…”
mentioning
confidence: 57%
“…Most of the studies found no correlation between having diabetes mellitus and quality of sleep in patients under chronic hemodialysis (2,10,11,13,24). On the other hand, we and Einollahi et al (23) observed a lower quality of sleep in patients with diabetes mellitus.…”
mentioning
confidence: 57%
“…Sleep disorders, including delayed sleep onset, frequent awakening, restless leg syndrome, insomnia, and daytime sleepiness, are frequent in patients with end stage renal disease (ESRD) (2,(4)(5)(6)(7)(8). These symptoms affect sleep quality and consequently the quality of life of these patients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that increasing duration of dialysis, physical health, co-morbidities, burden of kidney disease, sexual function, dyspnea, pain, itching, mean corpuscular volume, serum albumin, and diabetes mellitus worsen the quality of sleep [2,3,9,10]. However, contradictory studies are also available that suggest that quality of sleep in MHD patients is not related to age, gender, biochemical parameters, and other factors mentioned above [4,6]. Sleep quality has been reported to be independent of type of dialysis, i.e., the MHD and peritoneal dialysis suggesting that it could be either the burden of illness or the biochemical parameters that govern the quality of sleep [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, one study did not find any correlation between the mortality and poor sleep among these patients [13]. Not only the mortality but the morbidity is also important and poor quality of life has been consistently reported in patients on MHD with poor quality of sleep [4,10,12,14]. Moreover, patients with poor quality of sleep are also prone to consume a number of medications, e.g., hypnotics, antidepressants, antihistaminics, and narcotics [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation